MAKNA PROSESI PERKAWINAN SUKU LAUJE DI DESA TINOMBO KECAMATAN TINOMBO KABUPATEN PARIGI MOUTONG - Sunuh, Sri Wahyuni (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2020)
This research aims to determine the meaning of the non-verbal messages contained in the Lauje Tribe Wedding Procession in Tinombo Village, Tinombo District, Parigi Moutong Regency. The type of research used is descriptive qualitative, with data collection techniques used being observation and interviews. The data analysis technique used in this research is qualitative data analysis, which is used without using calculations. The data is then described in the form of sentences or narratives, either obtained from interviews or observations. The results of the research show that in the marriage procession of the Lauje tribe there are symbols and meanings consisting of Kinesik: namely facial messages in the form of smiles that emerge from the faces of the bride and groom which are interpreted as a form of pleasure and joy, gestural messages in the form of movements when rubbing henna leaves on the two The bride and groom's palms are interpreted as praying for the two partners so that their married life will always be in harmony and will be kept away from divorce and the movements used by the bridal couple at the stage of Popopene (mother-in-law) which is interpreted as when the husband and wife come home from the garden and bring The crops from the plantation are what are cooked and eaten together. Apart from that, when the bride incorrectly carries out the stages in Popopene (father-in-law) it will have an impact on their marriage, whether it be on the bride in the household or on their children later. Paralinguistic: the sound of the sambra and drum which is interpreted as a warm welcome to the guests of the Olongian king. Artifactual: Kabayaa (echo) is yellow, symbolizing the descendants of the Olongian king; yellow sarong, symbolizing bravery when facing enemies; The milk chocolate colored jacket symbolizes being the head of the family.